Ship route planning based on intelligent mapping swarm optimization - Ma, Weihao; Han, Yueyi; Tang, Huan; Ma, Dongfang; Zheng, Huarong; Zhang, Yang (Computers & industrial engineering, 2023)
•A new strategy for simultaneously optimizing ship route and speed is proposed.•Carbon tax policy and weather information are considered.•A two-layer mapping swarm intelligence optimization algorithm is established.•Decision results can be adjusted according to the maneuverability of the ship. In this paper, we propose a new strategy for simultaneously optimizing ship route and speed using a hierarchical mapping method that takes into account different carbon tax models. Compared with the traditional route planning methods, the main novelty of the proposed method is to separate the decision-making and weather information layers, which allows us to directly obtain the ship route and speed decision plan that conform to the ship’s maneuverability and crew habits. The key algorithmic contribution is a bi-layer mapping intelligent optimization algorithm, which establishes the mapping relationship between the upper and lower layers and a synchronous iterative update strategy. Case studies show that the designed method has significant advantages in both conventional and complex terrain ocean scenarios. Moreover, the sensitivity analysis showed that the proposed method can help shipping companies to better cope with rising fuel prices and various ship carbon tax models.